Generating self-financing for maintenance works case study - Institut Teknologi MARA / Muhammad Navil Mahmood - Mahmood, Muhammad Navil (1995)
Maintenance works for any type of building can be carried out efficiently with proper financial funding. The sufficient financial funding is needed in order for the maintenance management team to plan and organize a proper planning and control of the maintenance works to be carried out to an acceptable standard. Without sufficient funding, the maintenance manager will have to decide based on priorities and importance of the maintenance works to be carried out. At times, a lower standard of maintenance is carried out because of insufficient fund. The lower standard of maintenance which is being carried out, will eventually snowballed into bigger problem which in fact is far more expensive to rectified. Maintenance management is the management of available resources to maintain the 'building'. The existence of the building itself is to accomodate different people carrying various activities. Irrespective o£ public or private building, the management approach have to change. Instead of concentrating on the building alone, integration with people and their activities should be included in achieving the primary goal of the organization. In this aspect,the approach that should be adopted by organization in managing their assets efficiently is through Facilities Management.